2020
DOI: 10.1186/s12935-020-01168-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Circ_0008035 contributes to cell proliferation and inhibits apoptosis and ferroptosis in gastric cancer via miR-599/EIF4A1 axis

Abstract: Background: Currently, multiple circular RNAs (circRNAs) have been verified to act as essential regulators in the progression of gastric cancer (GC). We aimed to investigate the role of circ_0008035 in GC progression. Methods:Quantitative real-time polymerase chain reaction (qRT-PCR) was utilized to measure the expression of circ_0008035 and miR-599. 3-(4,5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide (MTT) assay was employed to evaluate cell proliferation and ferroptosis. Western blot assay was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 28 publications
2
51
0
Order By: Relevance
“…Furthermore, circ0008035 inhibited ferroptosis in gastric cancer via miR-599 /EIF4A1 axis. Knockdown of circ0008035 enhanced anticancer effect of erastin and RSL3 via increased iron accumulation and lipid peroxidation 156 . According to ferroptosis associated factors, in gastric cancer, circPVT1 promoted multidrug resistance by enhancing P-gp and GSTP.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, circ0008035 inhibited ferroptosis in gastric cancer via miR-599 /EIF4A1 axis. Knockdown of circ0008035 enhanced anticancer effect of erastin and RSL3 via increased iron accumulation and lipid peroxidation 156 . According to ferroptosis associated factors, in gastric cancer, circPVT1 promoted multidrug resistance by enhancing P-gp and GSTP.…”
Section: Introductionmentioning
confidence: 98%
“…Li et al found that Circ_0008035 promoted GC cell growth and repressed apoptosis and ferroptosis by upregulating EIF4A1 through sponging miR-599. 64 In addition, Zhang et al prove that exosome-miR-522 serves as a potential inhibitor of ALOX15. Further study demonstrates that Cancer-associated fibroblasts secrete exosome miR-522 to inhibit ferroptosis in cancer cells by targeting ALOX15 and blocking lipid-ROS accumulation.…”
Section: Othersmentioning
confidence: 99%
“…Among these ncRNAs, circular RNAs (circRNAs) are ideal biomarkers for human diseases due to their covalently closed loop structure [ 13 ]. Li et al claimed that circ_0008035 accelerated the progression of gastric cancer through regulating microRNA-599 (miR-599)/EIF4A1 axis [ 14 ]. CircPIP5K1A contributed to the development of gastric cancer through targeting miR-376c-3p/ZNF146 signaling [ 15 ].…”
Section: Introductionmentioning
confidence: 99%